The Effect of STEM Approach on Students' Critical Thinking Skills - Roza, Media; Azhar, Minda; Festiyed, F; Aswirna, Prima; Sari, Rika Purnama (Universitas Muhammadiyah Surakarta, 2023)
The influence of the STEM approach has been widely studied. However, a summary of how much influence STEM has on critical thinking skills from these various studies has not been done well. This article examines the impact of the STEM approach on students' capacity for critical thought when studying physics and science. This type of research is quantitative research with meta-analysis methods. Articles from recent four-year publications in national and international journals serve as data sources. Only 16 articles met the criteria for further analysis. This study's method of data analysis involved calculating the effect size to provide a summary effect size. There are four moderator variables analyzed: learning models, teaching materials, subject matter, and education level. Based on the study's findings, it can be said that the STEM approach to fostering students' critical thinking abilities has the largest impact size when used in motion systems courses at the high school level, using media schoology and worksheets for the students. The STEM approach is proven to have a high summary effect size on students' critical thinking skills, with a score of 1.37 (high category).